Isolation and identification of oligostilbene from the leaves of neobalanocarpus heimii using HPLC method / Muhammad Hakim Jaafar - Jaafar, Muhammad Hakim (2013)
Dipterocarpaceae is a plant family present in Malaysia consisting of a large number of plant species. This research aims to isolate and identify the chemical constituents of a species from Dipterocarpaceae, Neobalanocarpus heimii also known as chengal. This research was conducted by identifying known compounds from the crude extract using LCMS. Preparative High Performance Liquid Chromatography (HPLC) was used to isolate oligostilbene compound and was then purified using analytical HPLC. The purified compound was then analyzed using Proton Nuclear Magnetic Resonance (lH-NMR) spectroscopy to identify the compound structure and stereochemistry. The lH-NMR spectrum was then compared with the reported data from journals to identify the identity of the compound. As the summary, this research result shows that the leaves extract of Neobalanocarpus heimii contain oligostilbene which is vaticaphenol A.